Ausencia - Ureña, Jurgen, 1973-; Fallas, Erick; Alemán, Rebeca (Producciones La Ventana, 2010)
During a sleepless night, a lonely movie fan gets along with his best partner: the imagination. But, is it actually imagined everything that happens around him? Is it product of a sudden dream or of his anguished inability to sleep? Where are the boundaries between the cinema, the vigil and the dream? Ausencia is a short film about the creative solitude and about the movie fan's dreaming. It is the story of a man who lives his days and nights as a cinema character, an insomiac dreamer who believes, like the Spanish Luis Eduardo Aute, that everything in life is cinema and even dreams themselves are cinema. --